ANALYSIS OF COMPANY CAPABILITY USING 7S MCKINSEY FRAMEWORK TO SUPPORT CORPORATE SUCCESSION (CASE STUDY: PT X INDONESIA): ANALISA KAPABILITAS PERUSAHAAN DENGAN MENGGUNAKAN FRAMEWORK 7S MCKINSEY UNTUK MENDUKUNG KESUKSESAN PERUSAHAAN (STUDI KASUS: PT X INDONESIA) - Almira Devita Putri; Achmad Ghazali; Larasati Ahluwalia (Manajemen Bisnis, 2021)
PT X Indonesia is a telecommunications company with a geographically focused division which operating in the province of West Java. PT. X Indonesia is currently undergoing a digital transformation to achieve its goal of "becoming a leader in the digital region". However, this transition has accompanied with a large number of employees retiring between 2020 and 2021. This has resulted in increased workloads and a lack of competency. Therefore, PT X Indonesia will analyze its current capabilities, future capabilities, and existing gaps to meet future demand. This analysis uses a mixed method research model, where the current capabilities of PT X Indonesia are analyzed using a survey method. In addition, the researcher interviewed key informants at PT X Indonesia to find out the capabilities needed in the future. The 7s McKinsey's framework (1980) was used to analyze this research. This framework identifies seven dimensions that a company must possess to maintain its success. This 7s dimension consists of Strategy, System, Structure, Style, Skill, Staff, and Superordinate Goals. According to a survey conducted to assess the current capabilities of PT X Indonesia, there are three dimensions that are in the bottom three. Thus, to bridge the gap, there are several recommendations that must be immediately carried out by PT X Indonesia, namely strengthening the team work, recruiting new employees to fill vacancies, socializing the talent acquisition system, conducting coaching sessions from seniors, and conducting knowledge sharing.